Putting down the revolt: Enactivism as a philosophy of nature - Meyer, Russell; Brancazio, Nick (Frontiers in Psychology, 2022)
Enactivists frequently argue their account heralds a revolution in cognitive science: enactivism will unseat cognitivism as the dominant paradigm. We examine the lines of reasoning enactivists employ in stirring revolt, but show that none of these prove compelling reasons for cognitivism to be replaced by enactivism. First, we examine the hard sell of enactivism: enactivism reveals a critical explanatory gap at the heart of cognitivism. Drawing on Steiner (2019), we show that enactivism does not meet the requirements to incite a paradigm shift in the Kuhnian sense - there is no internal crisis in cognitivism. Nor does it provide inherently better explanations of cognition as some have claimed. Second, we consider the soft sell of enactivism: enactivism provides a more attractive, parsimonious, or clear-eyed lens on cognition. This move proves to boil down to a misunderstanding of how theories are selected in science. Instead we lend support to a broader and more desirable way to conceive of enactivism - Gallagher’s (2017) proposal that enactivism is a philosophy of nature. We explain how a philosophy of nature does more than support a single research paradigm by integrating scientific questions into a cohesive picture.